2022
DOI: 10.1186/s12903-022-02355-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of pharyngeal airway and maxillary arch in mouth and nasal breathing children with skeletal Class I and II

Abstract: Objective This study aimed to investigate whether the subjects with mouth breathing (MB) or nasal breathing (NB) with different sagittal skeletal patterns showed different maxillary arch and pharyngeal airway characteristics. Methods Cone-beam computed tomography scans from 70 children aged 10 to 12 years with sagittal skeletal Classes I and II were used to measure the pharyngeal airway, maxillary width, palatal area, and height. The independent t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Other dimensions like minimum constricted area and upper airway dimensions among other dimensions were also reported. Great interest and attention from orthodontists have been reported by research [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other dimensions like minimum constricted area and upper airway dimensions among other dimensions were also reported. Great interest and attention from orthodontists have been reported by research [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the location of the upper and lower jaws is associated with constriction of the anteroposterior aspect of the airway [ 13 ]. Upper airway obstruction and thus dysfunction leads to oral breathing which impacts craniofacial and skeletal morphology causing malocclusion [ 26 ]. Researchers have directed effort and attention towards cognizing the relationship between pharyngeal airway and dental anomalies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the evolution of CT-scans, readily available and widely used in dentistry, we have an ideal tool to assess the upper airway, soft tissues and tissue relationships. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Habumugisha et al [42] studied cone-beam CT images from 70 children aged 10 to 12 years in the sagittal position. These scans showed that the intermolar width, maxillary width of the molars, intercuspal width, maxillary width of cuspids and palatal area, were significantly greater in nasal-breathing patients than in mouth-breathing patients, thus indicating that the maxillary arch morphology of mouth-breathing children was narrower and longer than that of children in a nasalbreathing group.…”
Section: Lateral Alterationsmentioning
confidence: 99%